If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8+3x-12=3x-4
We move all terms to the left:
8+3x-12-(3x-4)=0
We add all the numbers together, and all the variables
3x-(3x-4)-4=0
We get rid of parentheses
3x-3x+4-4=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 3z-8=2z+15 | | 8=-5t+14t | | 7(-5x-4)=-57 | | -3a-8=14 | | 47x+2253x-12=46(50x+59) | | 4(x+4)=8x+14-4x+2 | | 2x+x/2-2+x=180 | | 6=6(2x-1) | | 3(x-6+4(7-x)=-27 | | 3(x-6)+(7-x)=-27 | | 5(4x-6)=-7 | | 8x+24=5x-9 | | 4x/5-(2x/3+5)=4x/6+3 | | |7-2x|=15 | | 5u-u=u+33 | | 0.1h(h+20)=3 | | 5x^2+30x=10 | | 2x+(2x)-14=100 | | 4=-2(x+4) | | -6(8+6n)-8=30+7n | | -4r=2 | | Y=8/4x+-10 | | 5-z=-14 | | 3(q+1)=6 | | -9(n-4)=5-(n-4) | | 6(5x+7)=-108 | | -8+z/2=2 | | -(v+-1)+-5=0 | | 12n+4=34-3n | | -28=2u+5u | | 6(3x-2)-3(4+5)=33 | | 8^x^2-32=64^2x |